Enhancing Core Mathematical Literacy in Primary School Students: Strategies and Implications for Sports Education and Cognitive Development - Chao Liu; Ting Ji (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
In the 21st century, core literacy has emerged as a critical focus in education, emphasizing the holistic development of students. While the concept of core literacy is relatively new, it aligns with the principles of quality education and curriculum reform in China, reflecting the fundamental laws of teaching innovation. This study explores strategies for cultivating primary school students’ core mathematical literacy, with implications for cognitive development and problem-solving skills, which are essential in sports education and team dynamics. Using a combination of literature review, questionnaires, interviews, and case analysis methods, this research addresses two key issues: (1) A survey and interviews with primary school mathematics teachers were conducted to assess their understanding of core mathematical literacy and their teaching abilities. Through quantitative and qualitative analysis, the study identifies the current practices and challenges in teaching mathematics to develop students’ core literacy; (2) Based on theories of professional development, the study examines cases to propose strategies for enhancing teachers’ abilities to foster mathematical literacy in students. These strategies include emphasizing mathematical cognition and in-depth teaching methods, improving students’ mathematical thinking by advancing teachers’ theoretical knowledge, cultivating mathematical emotions through teacher-student communication, and fostering a mathematical spirit in a supportive teaching environment. The findings indicate that implementing these strategies can significantly enhance the integration of core literacy into classroom teaching, improving teaching quality by over 28%. These insights have broader implications for sports education, where fostering cognitive, emotional, and strategic thinking skills can contribute to better performance, teamwork, and holistic development.